2018
DOI: 10.1007/s10439-018-02124-w
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Models for Studying Transport Across Epithelial Tissue Barriers

Abstract: Epithelial barriers are the body's natural defense system to regulating passage from one domain to another. In our efforts to understand what can and cannot cross these barriers, models have emerged as a reductionist approach to rigorously study and investigate this question. In particular, in vitro tissue models have become prominent as there is an increased exploration of understanding biological molecular transport. Herein, we introduce the pertinent physiology, then discuss recent studies and approaches fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 163 publications
0
29
0
Order By: Relevance
“…Some investigations have shown that oncogene-transfected hBMECs operate as same as primary cells. As transfected hBMECs have shown good barrier tightness and paracellular permeability, these cell lines are considered promising for establishing an in vitro BBB model ( Arumugasaamy et al, 2019 ). Brain endothelial cells derived from iPSCs (induced pluripotent stem cells) and hematopoietic stem cells are also used to develop BBB models ( Appelt-Menzel et al, 2017 ).…”
Section: Advancements In Predicting the Nanotoxic Effects On Biological Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigations have shown that oncogene-transfected hBMECs operate as same as primary cells. As transfected hBMECs have shown good barrier tightness and paracellular permeability, these cell lines are considered promising for establishing an in vitro BBB model ( Arumugasaamy et al, 2019 ). Brain endothelial cells derived from iPSCs (induced pluripotent stem cells) and hematopoietic stem cells are also used to develop BBB models ( Appelt-Menzel et al, 2017 ).…”
Section: Advancements In Predicting the Nanotoxic Effects On Biological Barriersmentioning
confidence: 99%
“…Microfluidic BBB models will soon replace animal testing to be employed in scientific and clinical research. Advanced microfluidics may represent the future of BBB models due to their design flexibility, capacity to combine coculture methods, and compliance ( Arumugasaamy et al, 2019 ). In addition, novel modeling techniques based on the culture of brain spheroids and organoids were established a few years earlier.…”
Section: Advancements In Predicting the Nanotoxic Effects On Biological Barriersmentioning
confidence: 99%
“…Moreover, quantitative MRI (qMRI) techniques have emerged as methods that reflect cartilage composition and health. 11 , 30 , 31 Specifically, qMRI measures such as T1rho and T2 relaxation times are sensitive to changes in proteoglycan concentration, collagen content and organization, and water content, 11 , 18 , 30 , 45 and can be obtained noninvasively. Studies have also shown that these qMRI measures change during OA progression, 20 , 28 31 , 35 motivating their use as indicators of cartilage health.…”
Section: Introductionmentioning
confidence: 99%
“…Skin is composed of multiple stratified layers that act as a protective barrier against external mechanical and biochemical factors (Arumugasaamy, Navarro, Kent Leach, Kim, & Fisher, ; Zhang & Michniak‐Kohn, ). Mammalian skin layers include the epidermis, dermis, and hypodermis.…”
Section: Introductionmentioning
confidence: 99%
“…The interactions between layers allow for skin to be an efficient barrier and any damage to it causes immediate compromised thermoregulation, fluid shifts, and risk of sepsis (Arumugasaamy et al, ; Markeson et al, ; Peck, Molnar, & Swart, ). Also, blood vessels and nerves grow along the interfaces of these layers forming the vascular plexuses; a lack of synergistic development of the layers results in deficient vascularization and innervation which impairs skin function (Kolarsick et al, ; Markeson et al, ; McLafferty et al, ; Wong et al, ).…”
Section: Introductionmentioning
confidence: 99%